The Impact of the Work Environment on Fatigue of Production Workers at PT X: External Factor Analysis - Sekar Ayu Lintang Pradita; Septia Dwi Cahyani; Irfany Rupiwardani (PROMOTOR, 2026)
The acceleration of industrial and economic growth, along with increasing population mobility, has contributed to the continuous expansion of business activities each year. This development pushes companies in Indonesia to advance toward industrialization, often resulting in extended working hours to meet production demands. Consequently, work fatigue has become a common issue in industrial environments, influenced by various factors, including external environmental conditions. This study aims to analyze the relationship between external environmental factors and work fatigue among production workers at PT X. The research employed an observational analytic design with a cross-sectional approach. The study involved 49 respondents from the erema production unit. Data were collected through interviews using the IFRC questionnaire to measure subjective fatigue levels, complemented by direct workplace observations. Bivariate analysis was conducted using binary logistic regression, while multivariate analysis employed ordinal logistic regression. The results indicated that environmental temperature and lighting significantly affected work fatigue, whereas working hours, workload, humidity, and noise showed no significant relationship. Among all variables, lighting was identified as the most dominant factor associated with work fatigue (p-value = 0.011; P < 0.05)